Uji Aktivitas Antibakteri Sabun Cair Ekstrak Metanol Daun Mangga Arum Manis (Mangifera indica L. var. arum manis) Terhadap Staphylococcus epidermidis - Bahrisy, Afif Hussein Kholid; Fitriyati, Laeli; Kiromah, Naelaz Zukhruf Wakhidatul (Prosiding University Research Colloquium, 2021)
Soap making has been done liquid soap preparation safer use of the nature ingridients an extract methanol leaves mango arum manis (Mangifera indica L. var. arum manis). The kind of research this is experimental. Extract was obtained through means tektik maceration with methanol solvent. Liquid soap made into three formulation with the variation of concentration extract F1 7,81g/mL; F2 15,53g/mL; and F3 62.5g/mL then it will be physical test and zone clear on Staphylococcus epidermidis bacteria with the methods sumuran, Control negative uses a base soap and control positive for the liquid soap in circulation stood in line. The data obtained tested use of One Way ANOVA. This research result indicates that liquid soap formula 1, 2 and 3 meet physical evaluation preparation except its viscosity and free alkali. Formula 1, 2 and 3 having antibacterial activity zone each with a diameter of an obstruent 8,75mm; 10,6mm; and 12mm. Liquid soap preparation formula 1, 2 and 3 having the difference meaningful and control positive and negative control with a value of p<0.05. Liquid soap preparation antibacterial activity every meaningful having the difference with p<0.05 percentage point. Variation concentration extract methanol leaves mango (Mangifera indica L. var. arum manis) to affect their antibacterial activity of Staphylococcus epidermidis. Formula 3 by concentration of the extract 62,5g/ml antibacterial activity have the best compared to a formula 1 and 2.